At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Complete the solution of the equation. Find the value of [tex]$y$[/tex] when [tex]$x = -7$[/tex].

[tex]-7x - 5y = 54[/tex]


Sagot :

Sure! Let's find the value of [tex]\( y \)[/tex] when [tex]\( x \)[/tex] is equal to -7 in the equation:
[tex]\[ -7x - 5y = 54 \][/tex]

### Step-by-Step Solution:

1. Substitute [tex]\( x = -7 \)[/tex] into the equation:
[tex]\[ -7(-7) - 5y = 54 \][/tex]

2. Simplify the substituted value:
[tex]\[ 49 - 5y = 54 \][/tex]

3. Re-arrange the equation to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ 49 - 54 = 5y \][/tex]

4. Simplify the difference:
[tex]\[ -5 = 5y \][/tex]

5. Solve for [tex]\( y \)[/tex] by dividing both sides by 5:
[tex]\[ y = \frac{-5}{5} \][/tex]
[tex]\[ y = -1 \][/tex]

### Conclusion:
The value of [tex]\( y \)[/tex] when [tex]\( x = -7 \)[/tex] is:
[tex]\[ y = -1 \][/tex]

Thus, substituting [tex]\( x = -7 \)[/tex] into the original equation [tex]\( -7x - 5y = 54 \)[/tex] gives us [tex]\( y = -1 \)[/tex].